Biaya Transaksi dan Periode Pemegang Saham Biasa yang Terdaftar di Bursa Efek Jakarta Periode 2002-2004 - Agus Zaenul Arifin; Tan Grace Tanzil (Jurnal Siasat Bisnis, 2008)
The purpose of this research is to investigate the influence of transaction costs for the period of shareholding. This research is a replication of the Atkins and Dyl (1997). The first part of the invested transaction cost which represented the bid-ask spread on the holding period. On the Atkins and Dyl (1997) research had added the control variables as independent variables in the form of market value and variance of stock returns. This research employs 30 companies has been taken as sample deemed all of the criteria on period 2002-2004. Analysis of the hypothesis was taken using 2SLS (two stage least square) regression. The result of this research indicate that the bid-ask spread, market value, and variance of stock return have a significant influence on the holding period of shares registered in Jakarta Stock Exchange. Keywords:    transaction cost, bid-ask spread, holding period, market value, variance of stock return